Presentation Structure and Symbolic Meaning of Sekapor Sireh Dance: An Ethnochoreological Study - Romi Faisal; Malarsih Malarsih (Gondang: Jurnal Seni dan Budaya, 2026)
Sekapor Sireh Dance is a welcoming dance of the Pontianak Malay community performed in customary, cultural, and state ceremonies. As a cultural product, the dance functions not only as an aesthetic performance but also as a medium for expressing cultural values and symbolic meanings. This study aims to analyze the presentation structure and symbolic meanings of Sekapor Sireh Dance from an ethnochoreological perspective. The research employed a qualitative method with an ethnochoreological approach. Data were collected through observation, interviews, and documentation at Sanggar Bougenville, West Kalimantan, and analyzed using the interactive model of Miles and Huberman combined with ethnochoreological analysis. The findings reveal that the presentation structure of Sekapor Sireh Dance consists of movement, musical accompaniment, makeup, costumes, accessories, properties, and floor patterns that form an integrated performance system. The symbolic meanings of the dance are constructed through the interrelationships among these elements, representing values of respect, acceptance, hospitality, openness, prayer, protection, and the cultural identity of the Pontianak Malay community. From an ethnochoreological perspective, these meanings emerge through the interconnectedness of all presentation elements, which collectively form a system of cultural symbols.